Study on the Economic and Sociological Condition of Villages in UP: Understanding the Economic and Sociological Condition of Villages in Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This was a sociological study of Azamgarh town in Uttar pradesh . It is the primary miniature level town study directed in Azamgarh town of Uttar pradesh . The truism that India lives in its villages is as near reality now as it was in the pre-Independence time frame. More than fifty years of economic arranging after Independence has passed but most of the country's populace keeps on living in rural regions. Agribusiness and its unified exercises actually give business and pay to a considerable section of the number of inhabitants in the rural work power. There have been numerous progressions occurring in them throughout the most recent hundred years and they keep on occupying a position of significance in contemporary India (Beteille 2006 79). Atal has said that Indian villages are wrestling with the battle of progress and it is time again to „return to the villages and attract the forms of progress them once more' (Atal 2006 117). Sweeping changes of financial significance are being introduced by the villages themselves which are worked with by cognizant state endeavors from one viewpoint and developing administration on the other so individuals are roused to seek after their own objectives and expand on strategically, instructively and economically strong and useful framework (Saksena 2013 17). Oommen has expressed that the working of such elements can't be completely seen accurately except if the social designs of town society are considered in its altering point of view (Oommen 2006 x). In this light an enquiry into what has been occurring in the rural regions expects importance.